1972
DOI: 10.1111/j.1464-410x.1972.tb10144.x
|View full text |Cite
|
Sign up to set email alerts
|

THE URETEROVESICAL INNERVATION A New Concept Based on a Histochemical Study

Abstract: THE classical concept of the innervation of the urinary tract pretends that the ureter is supplied by sympathetic nerves while the bladder receives essentially parasympathetic nerves.Morphological studies of the intrinsic innervation of the urinary tract have been limited for decades by classical microscopic techniques (such as intravital methylene blue or silver impregnation) which could not establish the difference between sympathetic (adrenergic) and parasympathetic (cholinergic) nerves.The application of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…It may be attributed most probably to interspecies differences or to different stage of the development of this part of the peripheral nerve system, that is known to be able to make so-called "transmitter switch" in the presence of particular trophic molecules vide the plasticity of the sweat gland innervation (Landis and Fredieu 1986). The finding of such big proportion of noradrenergic neurons in the bladder wall is probably due to the fact that similarly to human all the ganglia presently examined came from the bladder trigone and neck where noradrenergic nerves have been shown to be concentrated (Schulman et al 1972), especially in males . In this region noradrenergic nerves have been shown to cause smooth muscle contraction and thus closure of the bladder neck (Lincoln and Burnstock 1993) and in the male such nerves are activated at the time of seminal emission and prevent the reflux of semen into the bladder (so-called "retrograde ejaculation") (Krane and Olsson 1973).…”
Section: Discussionmentioning
confidence: 86%
“…It may be attributed most probably to interspecies differences or to different stage of the development of this part of the peripheral nerve system, that is known to be able to make so-called "transmitter switch" in the presence of particular trophic molecules vide the plasticity of the sweat gland innervation (Landis and Fredieu 1986). The finding of such big proportion of noradrenergic neurons in the bladder wall is probably due to the fact that similarly to human all the ganglia presently examined came from the bladder trigone and neck where noradrenergic nerves have been shown to be concentrated (Schulman et al 1972), especially in males . In this region noradrenergic nerves have been shown to cause smooth muscle contraction and thus closure of the bladder neck (Lincoln and Burnstock 1993) and in the male such nerves are activated at the time of seminal emission and prevent the reflux of semen into the bladder (so-called "retrograde ejaculation") (Krane and Olsson 1973).…”
Section: Discussionmentioning
confidence: 86%
“…In their study they administered nicotine by intravenous, inhaled or topical route and shown that both intravenous and inhaled nicotine, although effective at different dosages, do alter the peristalsis of the ureter [5]. Nicotine most probably exhibits this effect on the ureter over the cholinergic receptors proven to be present in the ureter also [13]. Further studies have shown that in each breath of a cigarette smoked there is 120 μg nicotine and about 50% of this is absorbed to the circulation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In the cat De Groat and Saum (1972) have shown that stimulating the sympathetic system inhibits the parasympathetic centre. Anatomical interconnections have been disclosed in animal between sympathetic and parasympathetic systems in the pathways from the lumbo-sacral centres to the bladder and particularly in the ganglionic perivesical plexus (Schulman et al, 1972). The micturition parasympathetic centre could be under continuous inhibitory control from sympathetic origin as would be the case in patients with spinal cord lesions above the thoracolumbar sympathetic centre (McGurie et al, 1976).…”
Section: Discussionmentioning
confidence: 99%